Answers

2016-01-29T18:59:10+05:30
Given,
       LX=XY=YN
       XZ II LM
prove: ar (LZY)=ar(MZYX)
construction: join YZ,XM and LZ
proof:  ar(LZX)+(XZY)=ar(LZY)               --- (1)
           ar(MXZ)+ar(XZY)=ar(MZYX)        --- (2)
         
          ar(LZX)=ar(MXZ)       (both triangles are on the same base XZ and                                                             between same parallels LM and XZ)
          on adding equation (1) and (2) we get,
         ar(LZY)=ar(MZYX) 
          Hence proved
3 4 3
how much u understand from my answer according to that plz rate the answer
2016-01-29T19:39:20+05:30
U can get help by using the theorem triangles between same parallel lines and on same base
0